2000
DOI: 10.1128/iai.68.2.630-636.2000
|View full text |Cite
|
Sign up to set email alerts
|

A NovelLeishmania infantumRecombinant Antigen Which Elicits Interleukin 10 Production by Peripheral Blood Mononuclear Cells of Patients with Visceral Leishmaniasis

Abstract: We report here the characterization of a novel Leishmania infantum protein termed papLe22 (22-kDa potentially aggravating protein of Leishmania). A positive clone from a cDNA library was identified by serum of a visceral leishmaniasis (VL) patient. Full-length cDNA obtained using rapid amplification of cDNA ends-PCR codes for a 22-kDa protein. In L. infantum promastigotes an endogenous nuclear protein of 14-kDa electrophoretic mobility was found by using an antiserum prepared against the fusion protein glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…It has been shown that GM-CSF and TGF-␤ are involved in leukocyte recruitment in inflammatory responses, 30,31 and that they may have inhibitory effects on a macrophage's ability to kill intracellular pathogens. 10 Given that L. donovani-and L. chagasiinfected mice also lack IL-4-dominance in disease development 32,33 and that a mixed Th1/Th2 response is a characteristic feature in L. infantum-and L. braziliensis-infected patients, [34][35][36] it is important to further examine factors responsible for susceptibility of a host to these Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that GM-CSF and TGF-␤ are involved in leukocyte recruitment in inflammatory responses, 30,31 and that they may have inhibitory effects on a macrophage's ability to kill intracellular pathogens. 10 Given that L. donovani-and L. chagasiinfected mice also lack IL-4-dominance in disease development 32,33 and that a mixed Th1/Th2 response is a characteristic feature in L. infantum-and L. braziliensis-infected patients, [34][35][36] it is important to further examine factors responsible for susceptibility of a host to these Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…After screening two expression L. infantum cDNA libraries with an acute-phase VL patient serum a 214-bp lambda gt11 insert was selected and sequenced of as described previously [29]. Then, the 267-bp ORF of Lepp12 was obtained using RACE-PCR on retrotranscribed promastigote mRNA, as indicated in the Methods section [29].…”
Section: Resultsmentioning
confidence: 99%
“…Then, the 267-bp ORF of Lepp12 was obtained using RACE-PCR on retrotranscribed promastigote mRNA, as indicated in the Methods section [29]. Figure 1 shows the deduced 87 amino acid sequence of predicted molecular weight of 11.6 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, LACK does not induce lymphoproliferation in patients cured of VL, 52 and papLe22 elicits production of IL-10 but not IFN-γ. 53 Both antigens play a prominent role in the pathogenesis of Leishmania infection in patients with different clinical presentations. 53,54 However, vaccine strategies, such as DNA or prime-boost vaccinations, which are able to induce a strong T h 1 immune response against these antigens, have proven able to obtain protection against L. infantum , probably by promoting a redirection of their T h 2 immune response to a T h 1 profile.…”
Section: Discussionmentioning
confidence: 99%
“…53 Both antigens play a prominent role in the pathogenesis of Leishmania infection in patients with different clinical presentations. 53,54 However, vaccine strategies, such as DNA or prime-boost vaccinations, which are able to induce a strong T h 1 immune response against these antigens, have proven able to obtain protection against L. infantum , probably by promoting a redirection of their T h 2 immune response to a T h 1 profile. 30,55 The lack of a standardized antigen is the main drawback of the LST.…”
Section: Discussionmentioning
confidence: 99%